GAMBAR INFORMASI - M. Umar Hadi (Ars: Jurnal Seni Rupa dan Desain, 2008)
/Is an applied art, Visual Communication Design is expected tobe able to deliver information effectively.When understanding the issue, a designer would realise that drawing is not merely presenting beauty butshould be o f meaning to the audience. Depicting information is not an easy matter because its spirit is toprovide a service to the public through an easily absorbed sign ur visual language.Each target group has a different background such as geography, psychography, social status, etc.,which influences their absorptive capability towards an oltject. This becomes a subject fo r those who studyat the Visual Communication Design department so as to be able to present appropriate information. Ir.fact, Otto Net/rath - with his ISOTYPE - has inspired them to design effective symbols for the publicUsing a simple form, representing objects appropriately can make a picture become more informative.Keywords: picture, information